Circulating CD21(low) B cells in common variable immunodeficiency resemble tissue homing, innate-like B cells - Rakhmanov, Mirzokhid (National Academy of Sciences, 2009)
The homeostasis of circulating B cell subsets in the peripheral blood of healthy adults is well regulated, but in disease it can be severely disturbed. Thus, a subgroup of patients with common variable immunodeficiency (CVID) presents with an extraordinary expansion of an unusual B cell population characterized by the low expression of CD21. CD21(low) B cells are polyclonal, unmutated IgM(+)IgD(+) B cells but carry a highly distinct gene expression profile which differs from conventional naïve B cells. Interestingly, while clearly not representing a memory population, they do share several features with the recently defined memory-like tissue, Fc receptor-like 4 positive B cell population in the tonsils of healthy donors. CD21(low) B cells show signs of previous activation and proliferation in vivo, while exhibiting defective calcium signaling and poor proliferation in response to B cell receptor stimulation. CD21(low) B cells express decreased amounts of homeostatic but increased levels of inflammatory chemokine receptors. This might explain their preferential homing to peripheral tissues like the bronchoalveolar space of CVID or the synovium of rheumatoid arthritis patients. Therefore, as a result of the close resemblance to the gene expression profile, phenotype, function and preferential tissue homing of murine B1 B cells, we suggest that CD21(low) B cells represent a human innate-like B cell population.